CEO problem based analysis of D2D cooperative user pairing - Xin He; Juntti, Markku; Xiaobo Zhou; Komulainen, Petri; Matsumoto, Tad (SPAWC : signal processing advances in wireless communications, 2015)
We interpret the device-to-device (D2D) cooperative relaying framework as an instance of a two-node binary chief executive officer (CEO) problem. Noise-corrupted versions of a binary sequence are transmitted by two nodes to a single destination node over orthogonal multiple access channel. A lower bound of the bit error probability (BEP) is obtained by minimizing a distortion function subject to constraints on inequalities based on the source-channel separation theorem. We derive the rate-distortion function for a binary multiterminal source coding problem. The distortion function is then established by evaluating the relationship between two problems for majority and optimal decision criteria. Our proposed encoding/decoding algorithms using concatenated convolutional codes and joint decoding scheme are used to verify the lower bound of the BEP. The results are interpreted as a criterion to select cooperating D2D user pairs.